2012
DOI: 10.1161/jaha.112.001842
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles Induce Cell Cycle Arrest Through Redox‐Sensitive Processes in Endothelial Cells: Implications in Vascular Senescence

Abstract: BackgroundChronic disease accelerates endothelial dysfunction in aging, a process associated with cell senescence. However, the mechanisms underlying this process are unclear. We examined whether endothelial cell (EC)-derived microparticles (MPs) facilitate EC senescence and questioned the role of reactive oxygen species in this process.Methods and ResultsSenescence was induced by sequential passaging of primary mouse ECs. Cells retained phenotypic characteristics of ECs from passage 4 through passage 21. Pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 51 publications
3
74
0
Order By: Relevance
“…These data are consistent with our previous reports identifying ROCK as a determinant of endothelial MP formation and highlight the critical role of cytoskeletal reorganization in MP formation. 22,23 A key finding in the present study is that podocyte-derived MPs are present in urine at the earliest stages of diabetic renal injury. Indeed, in STZ-treated mice, podocyte MPs were detectable in urine in advance of albuminuria.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…These data are consistent with our previous reports identifying ROCK as a determinant of endothelial MP formation and highlight the critical role of cytoskeletal reorganization in MP formation. 22,23 A key finding in the present study is that podocyte-derived MPs are present in urine at the earliest stages of diabetic renal injury. Indeed, in STZ-treated mice, podocyte MPs were detectable in urine in advance of albuminuria.…”
mentioning
confidence: 57%
“…22,23 NTA Sizing and enumeration of extracellular vesicles were achieved by NTA using a Nanosight LM10 instrument (NanoSight Limited, Amesbury, UK) equipped with NTA 2.3 software. 30 NTA is a light-scattering technique that uses video analysis for sizing and enumeration of extracellular vesicles.…”
Section: Electron Microscopymentioning
confidence: 99%
“…In addition, it has been reported that endothelial MPs increased the production of O 2 − in rat aortic rings [54] and the MPs could promote endothelial cells senescence through NADPH oxidase and mitochondria ROS production [55].Therefore, it is believed that MPs produce the pro-oxidative effects and regulate ROS production. It seems that this property is depending on the source of MPs and the manner in which they are formed [48].…”
Section: Discussionmentioning
confidence: 99%
“…23,30 A total of 50 mg protein was used for analysis, and results are expressed as arbitrary units/mg protein.…”
Section: Caspase-3 Activitymentioning
confidence: 99%